Demarginalizing the intersection of race and sex: A black feminist critique of antidiscrimination doctrine, feminist theory and antiracist politics - Crenshaw, Kimberle (The University of Chicago Legal Forum, 1989)
Keywords: afro-féminisme; amériques; antiracisme; approches et analyses; cours; discipline; droit; féminismes noirs; incontournable; intersectionnalité; militance; pol4212; premier cycle; projet charge mentale; racisme; ressource en ligne; régions géographiques; science politique et droit; systèmes d'oppressions; thématiques; états-unis

Margaret Thatcher is my sister: Counselling on divisions between women - Itzin, Catherine (Women's Studies International Forum, 1985)
This paper looks at the ways in which women are divided from themselves and each other as women: at the internalised oppression which results from THE oppression of patriarchy, at the systematic mistreatment of women as a group by men as a group reinforced by the social structures of male power. It also looks at the ways in which women are divided from each other as a result of other oppressive systems such as class and/or race or religion or physical ability or age. The paper then describes how the particular theory and practice of Re-evaluation Counselling can be used to ‘deconstruct’ or ‘discharge’ the internalised oppression of patriarchy and other oppressive systems, making the principles of Women's Liberation and sisterhood a practical possibility for ‘everywoman’ and all women—including Margaret Thatcher. Throughout, the word ‘patriarchy’ is used to mean the system of male power usually regarded as synonymous with sexism.
Keywords: approches et analyses; capacitisme; militance; patriarcat; racisme; sororité; systèmes d'oppressions; thématiques; âgisme

Resistance to oppression: Black women's response to slavery in the united states - Ellison, Mary (Slavery & Abolition, 1983)
Keywords: afro-féminisme; amériques; approches et analyses; cours; esclavagisme; fem3100; femmes* afro-américaines; féminisme afroaméricain; histoire et politique; militance; premier cycle; racisme; régions géographiques; sexisme; systèmes d'oppressions; thématiques; violences; états-unis